Corporate actors in global governance : business as usual or new deal? - Hofferberth, Matthias (Lynne Rienner Publishers, Inc., 2019)
What part do/should corporate actors play in global governance? With regard to concerns over such issues as public health, education, human rights, and the environment, they arguably are influential. But what is the actual nature of their engagement, and what motivates it? What challenges do they face when they assume more responsibility in these spheres? Are they responsive to the normative environments in which they operate? In answering these questions, the authors of Corporate Actors in Global Governance offer an empirically rich picture of the often contentious governance roles of corpora.